Reconstruction Model in Filling the Regional Head Position from the Perspective of State Administrative Law and The Fourth Principle of Pancasila - Zulwisman Zulwisman; Hengki Andora (PT. Anagata Sembagi Education, 2026)
This article analyzes the process of filling regional head positions in Indonesia and reconstructs its model from the perspective of State Administrative Law and the fourth principle of Pancasila. The research uses normative legal methods with statutory, conceptual, and historical approaches. The results indicate that the regulation of filling regional head positions has evolved toward a more structured direct electoral democracy, but still faces fundamental weaknesses, namely the dominance of political parties in the nomination process, high political costs, money politics, overly procedural democracy, single candidates, and the widespread use of acting regional heads. These conditions indicate that the current system does not fully align with the principles of State Administrative Law and the values of the fourth principle of Pancasila. This research proposes a reconstruction of a model for filling regional head positions that is administrative-deliberative in nature, with electoral legitimacy maintained through more proportional access to nominations, strengthening public deliberative forums, and stricter restrictions on the appointment of acting regional heads.